Middle meningeal artery embolization without surgical evacuation for chronic subdural hematoma: a single-center experience of 209 cases - Orscelik, Atakan; Senol, Yigit Can; Bilgin, Cem; Kobeissi, Hassan; Arul, Santhosh; Cloft, Harry; Lanzino, Giuseppe; Kallmes, David F.; Brinjikji, Waleed (Frontiers in Neurology, 2023)
Background: Middle meningeal artery (MMA) embolization is a minimally invasive treatment option for new and recurrent chronic subdural hematoma (cSDH).Objective: To examine the safety and efficacy profile of MMA embolization without surgical evacuation for cSDH patients.A single-center retrospective study of patients with cSDHs treated by MMA embolization was performed. Patient demographics, hematoma characteristics, procedural details, and clinical and radiological outcomes were collected. The primary outcome was the need for retreatment, and the secondary outcomes were at least 50% reduction in the maximum width of cSDH on the last CT imaging, complications, and improvement in modified Rankin scale (mRS) score. All results were presented as descriptive statistics.Results: A total of 209 MMA embolizations were successfully performed in 144 patients. Polyvinyl alcohol particles were the primary embolization agent in all procedures. Of total 206 cSDHs, the median maximum width on pre-intervention and the last follow-up were 12 and 3 mm, respectively, the median reduction percentage was 77.5%, and >50% improvement on the last follow-up imaging was observed in 72.8%. A total of 13.8% of patients needed retreatment for recurrent, refractory, or symptomatic hematoma after embolization. mRS score improved in 71 (49.3%) patients. Of total 144 patients, four (2.8%) experienced complications related to procedure and twelve (8.4%) died during the follow-up due to causes unrelated to the MMA embolization procedures.This study supports that MMA embolization without surgical evacuation is a safe and effective minimally invasive option for the treatment of cSDHs.